Pd-like controllers for delayed bilateral teleoperation of manipulators robots - Slawiñski, Emanuel (2015)
This paper proposes a compensated PD-like controller for delayed bilateral teleoperation of a manipulator robot. The scheme has a PD-like remote controller, a damping into the master, and a compensation strategy. The proposed compensation removes part of potential energy of the user´s command depending on the difference between the situation on the remote site and the situation as perceived by the human operator. In addition, the stability of the delayed teleoperation system is analyzed, and a comparison based on experiments is carried out in order to analyze the advantages of using the proposed compensation. Finally, results of a bilateral teleoperation including the proposed control scheme, where the master and slave exchange information by using a low-cost connection of mobile Internet, are shown.